AEGIS-AcutE Geriatric Intervention Study: pilot study of frontline acute geriatric assessment to improve quality of care in emergency department - Karjalainen, Kaisa J.; Tuori, Hannele; Salminen, Marika; Peltonen, Juha; Rantanen, Sirpa; Viikari, Paula; Viitanen, Matti; Nuotio, Maria S.; Viikari, Laura (OXFORD UNIV PRESS, 2025)
Introduction: Due to the increasing number of older patients in emergency departments (EDs) with frailty, cognitive impairment and multimorbidity, there is a need for geriatric expertise in EDs.
Methods: This retrospective study is of older patients visiting Turku University Hospital ED between 2 January and 31 December 2022. Patients aged 75 years of older were screened for frailty using Triage Risk Screening Tool (TRST) and Clinical Frailty Scale (CFS). Nonacute, frail patients (CFS >= 4) suitable for Targeted Geriatric Assessment (TGA) (n = 1096) were scanned for the risk of delirium, cognitive impairment, change in functional status, falls, malnutrition and depression. A comprehensive patient record was made with recommendations for future care.
Results: TRST was completed in 70% of the ED visits, and two-thirds of those were considered high-risk. Among the patients assessed by the geriatric team (TGA), nonspecific complaint (38%) and falls (35%) were the main reasons for ED admission. Cognitive impairment was present in over 60% and orthostatic hypotension in 40% of the patients. The 72-hour revisit rate for TGA-patients was 2.3%. For the real-life control group, the 72-hour revisit rate was 4.6% (P = .001). Thirty-day revisit rates were 10% and 16%, respectively (P < .001). The need for rehabilitation, cognitive evaluation and intensifying home care were the main recommendations for future care.
Conclusions: TGA approach provides structured and accurate information on older patients' background. This may lead to more precise diagnostics, a thorough consideration of hospital intake and a secure discharge from the ED. Ensuring continuity of care may help to reduce readmissions to EDs.